HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN PENALARAN ILMIAH PESERTA DIDIK DI SMA NEGERI 10 PALEMBANG - Setioningrum, Putri (Jurnal Pengajaran MIPA, 2021)
The purpose of this research was to find out the relation between critical thinking abilities and scientific abilities of the students at senior high school 10 Palembang. The method used in this research is correlation with random sampling techniques. The research sample consisted of 69 students of class XI MIA. The reserarh data was taken with instrument questions of critical thinking abilities collection techniques and Lawson’s Classroom Test of Scientific Reasoning (LCTSR) for scientific reasoning questions which were distributed via google form. The result of the research showed that the critical thinking abilities of students were in the poor category with an average value of 43,30 and majority of the students’s scientific reasoning abilities were at the level operational concrete with a percentage of 88,41%. The result of the correlation test between critical thinking abilities and scientific reasoning abilities of the students showed a positive correlation with low interpretation namely the correlation coefficient of 0,250.Keywords: Correlation, Critical Thinking Abilities, Scientific Reasoning Abilities.